AKTIVITAS DAN EFEKTIVITAS ANTIBAKTERI EKSTRAK DAUN CIPLUKAN (Physalis angulata L.) TERHADAP PERTUMBUHAN Bacillus cereus - Tiara Dini Harlita; Nurul Anggrieni; Ardiana Finda Widya Rahmawati (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2019)
Ciplukan leaf (Physalis angulata L.) is one of the plants used by the community as an alternative to avoid side effects of antibiotics. This plant has traditionally been used to cure various diseases. Potential leaf ciplukan as medicinal plants suspected due to the active compounds active ingredients contained in it. This study aims to test the activity and effectiveness of the antibacterial ethanol extract of ciplukan leaf on the growth of Bacillus cereus. Ciplukan leaf were extracted by maceration method using ethanol 96%. Each concentration was tested for antibacterial activity against B.cereus using disc diffusion method. The determination of minimum inhibitory concentrations by solid dilution. Data were analyzed with ANOVA at 95% confidence level. The test results showed that ciplukan leaf ethanol extract (P. angulata L.) had activity and effectiveness on B. cereus growth in vitro. The most effective concentration of ciplukan leaf ethanol extract can inhibit the growth of B. cereus is 30 mg/mL with inhibit zone of 24.2 mm. The minimum inhibitory concentration of ciplukan leaf ethanol extract on B. cereus growth was 5 mg/mL.